Avaliação da fertilidade físico-hídrica de sulcos de plantio em cambissolo manejado na cafeicultura - Pereira, Fernandes Antônio Costa (2021)
Brazil is the world's largest coffee producer, with an expressive contribution to its national economy. Crops implanted in soils considered of low agricultural suitability, such as an Inceptisol (Cambissolo Háplico Distrófico), associated with the occurrence of long periods of drought, can be a challenge for coffee production. Crops on this soil class are subject to production losses due to their low physical-hydric fertility, especially when not properly managed. Mechanical preparation of the planting furrow, as part of a management system, is a crucial step for the proper establishment of the crop. Long-term soil physical quality assessments in these tillage systems are still required for a correct technical recommendation. However, these assessments usually require a large number of samples, which, in addition to being costly, can cause destruction of the body under study, which may make long-term research unfeasible. In this context, the objective of the present work was to evaluate the physical conditions of coffee planting furrows using less invasive and destructive methods. The experiment was installed in an area located in the municipality of Nazareno-MG. Planting was carried out on December 23, 2015, with the cultivar Catuaí Vermelho – IAC 99 (Coffea arabica L.). The adopted spacing was 3.6 m between planting lines and 0.75 m between plants. To open the planting furrows, which distinguishes the treatments, three types of implements were used: at T40, a furrower was used to prepare the soil up to 40 cm in depth; for T60, a soil tiller (mix) up to 60 cm was used; and at T80, a subsoiler was used for preparation up to 80 cm and a mix for soil tillage up to 60 cm. Field penetration resistance assessments were carried out in December 2019, using an impact dynamic penetrometer. On the same occasion, samples were collected to adjust models for the Water Retention Curve (CRA) and the Least Limiting Water Range (IHO) as a function of the soil compaction degree (GC). Through the analysis of the penetrometer carried out in the field and in the laboratory, it was possible to predict the GC of these profiles. Undisturbed samples were collected in two randomly chosen trenches to perform a correlation analysis between the observed and predicted results by the penetrometer analysis. There was a strong positive linear correlation (r = 0.81) between the observed degree of compaction and the predicted degree of compaction. The increase in GC caused significant changes in the shape of the CRAs. The IHO increased as a result of the increase in the CG up to 80%. Aeration porosity was the first limiting factor, followed by soil mechanical impedance. GC values close to or above 88% represent a condition of extreme physical limitation. All the methods used to prepare the planting furrow were crucial to ensure better physical-hydric fertility. The treatments in which the planting furrow was prepared using a mix had a greater volume of soil potentially exploitable by the roots.